2014
DOI: 10.1080/10590501.2014.907460
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics and Cancer Susceptibility: Advances with Next-Generation Sequencing

Abstract: The aim of this review is to comprehensively summarize the recent achievements in the field of toxicogenomics and cancer research regarding genetic-environmental interactions in carcinogenesis and detection of genetic aberrations in cancer genomes by next-generation sequencing technology. Cancer is primarily a genetic disease in which genetic factors and environmental stimuli interact to cause genetic and epigenetic aberrations in human cells. Mutations in the germline act as either high-penetrance alleles tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 213 publications
(213 reference statements)
0
20
0
Order By: Relevance
“…In some cases the altered expression of DMEs contributes to disease susceptibility and to variations in drug efficacy and drug safety [23,30]. For a well-known example that is relevant to this study, CYP2E1 catalyzes the bioactivation of acetaminophen (APAP) to produce a reactive metabolite that leads to liver injury [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases the altered expression of DMEs contributes to disease susceptibility and to variations in drug efficacy and drug safety [23,30]. For a well-known example that is relevant to this study, CYP2E1 catalyzes the bioactivation of acetaminophen (APAP) to produce a reactive metabolite that leads to liver injury [31].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades a number of pharmacogenetics studies have reported genetic variations within the promoters, coding regions, and 3′-UTRs of DME genes that are associated with significant functional effects on drug metabolism that influence drug safety and efficacy [30,33]. Recently, additional mechanistic insights have been gained from studies into epigenetic mechanisms that are also involved in the regulation of DME gene expression [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence documented that miRNAs play an important role in the modulation of the production of drug metabolizing enzymes and transporters through multi-directional interactions among environmental stimuli, the expression of miRNA molecules and genetic polymorphisms [26][27][28][29][30][31][32][33]. As miRNA expression has been reported to be affected by drugs and since miRNAs themselves may affect drug metabolism and toxicity, miRNA expression possesses a significant potential for affecting drug efficacy and drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that xenobiotics influence the expression of NRs [30,31] and DMETs [3234]. Similar to mRNA expression, the expression of miRNAs is tightly controlled by transcription factors [35] that are responsive to environmental challenges, including dietary constituents or metabolites derived from the diet, pollutants and other xenobiotics [9,36]. In addition, the expressions of miRNAs, NRs and DMETs are modulated by single nucleotide polymorphisms (SNPs), which lead to great interindividual variability in drug efficacy and safety.…”
Section: Impact Of Mirna On Pharmacogenomics: Interindividual Variabimentioning
confidence: 99%